Gestión de rutas a través del uso de modelos basados en algoritmos - Bravo Quispe, Ana Paula (2021)
It is known that routing problems in logistics planning are of high importance for organizations, generating from economic problems to setbacks in all operations of the supply chain. For this reason, several professionals dedicated to logistics operations have focused on optimizing models that can solve this problem, which affects both directly and indirectly to internal and external processes of organizations. For this reason, this paper will review the literature, which identifies the importance of optimizing the routes that are developed for logistics processes and the supply chain nowadays, also analyze the approach of the concepts proposed by various authors, as well as the models of vehicle routing problems including the description for each of the types of classification, then describe some of the most used methodologies for solving the VRP. Subsequently it was determined according to the information presented, that the most used algorithms at present for the development of models of optimization of management and elaboration of routes are the heuristics, metaheuristics, exact and matheuristics, concluding that the latter is the best due to its flexibility and adaptability to the different restrictions that are applied, as well as the problems that arise derived from the different logistics processes. Finally, it will be shown a model made by the National University of Colombia in which a memetic algorithm (metaheuristics) is used for a problem of pickup and delivery of merchandise, in which it is demonstrated that the use of this type of algorithms for the creation of models can be of help for the improvement of the processes looking for improve the efficiency.